A teologia como “intellectus amoris”. A propósito de crítica de Clodovis Boff a Jon Sobrino - Aquino Júnior, Francisco de (Revista Eclesiástica Brasileira, 2019)
O debate atual sobre a TdLe seu método tem seu ponto de partida e uma de suas objetivações privilegiadas na crítica de Clodovis Boff à tese de Jon Sobrino da TdL como “intellectus amoris”. Ela revela a existência de conflito entre duas concepções bem distintas e, sob certos aspectos, contrárias ao quefazer teológico e, pressupostamente, ao conhecimento humano em geral. É o que procuraremos explicitar nesse artigo, apresentando a tese de Sobrino (I) e a crítica de C. Boff a essa tese (II) e discutindo criticamente a crítica de C. Boff (III). Abstract: The current debate about the Theology of Liberation and its method has as its starting point and as one of its primary expressions Clodovis Boff’s criticism of Jon Sobrino’s thesis about the Theology of Liberation as “intellectus amoris”. The debate reveals the existence of a conflict between two very different conceptions that are, under certain aspects, contrary to the theologian task and presumably also to human knowledge in general. This is what this article intends to explain by presenting both Sobrino’s thesis (I) and C. Boff’s criticism(II) and by discussing the latter in a critical manner (III).